STUDI KOMPARATIF: PENGELOLAAN WAKAF DI INDONESIA, MALAYSIA DAN SAUDI ARABIA (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2023)
The large role of waqf in the economy, has the potential to give birth to a very strong economic giant. The purpose of this study is to find similarities and differences in waqf management in Indonesia, Malaysia and Saudi Arabia. This study uses secondary data in the form of journals, annual reports, statistical data and various other sources that discuss waqf management in Indonesia, Malaysia and Saudi Arabia. Data collection was carried out through literature studies by studying books or scientific literature and journals to obtain comparisons of waqf management. This study uses secondary data in the form of journals, annual reports, statistical data and various other sources that discuss waqf management in Indonesia, Malaysia and Saudi Arabia. Data collection was carried out through literature studies by studying books or literature and scientific journals to obtain comparisons of waqf management in Indonesia, Malaysia and Saudi Arabia. This study uses a descriptive-comparative analysis method. In general, the management of waqf in Indonesia, Malaysia and Saudi Arabia is not much different, but in several respects, Indonesia has very fundamental differences in waqf management compared to Malaysia and Saudi Arabia.